2x-15x-53=0

Simple and best practice solution for 2x-15x-53=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-15x-53=0 equation:


Simplifying
2x + -15x + -53 = 0

Reorder the terms:
-53 + 2x + -15x = 0

Combine like terms: 2x + -15x = -13x
-53 + -13x = 0

Solving
-53 + -13x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '53' to each side of the equation.
-53 + 53 + -13x = 0 + 53

Combine like terms: -53 + 53 = 0
0 + -13x = 0 + 53
-13x = 0 + 53

Combine like terms: 0 + 53 = 53
-13x = 53

Divide each side by '-13'.
x = -4.076923077

Simplifying
x = -4.076923077

See similar equations:

| 8x+x^2=11 | | u(u)+5u+4=0 | | a^2-13a+10=0 | | 20-16t^2+32t=0 | | 3[6x-2(y-3)]= | | (3X+5)+(2X-1)=(X-2)-(3X-4) | | x^3-6x^2+9x+2=x^2-7x+14 | | 2(7x+1)=14x+2 | | 5m^2-2m=m+3m^2 | | 3(5y+5)-4(y-3)= | | 0.3f=2.173 | | h=-49t^2+ct+k | | x^3-7x^2+16x-12=0 | | 0.08(y-2)+0.18y=0.16y-0.6 | | 0.08(y-2)+0.18=0.16y-0.6 | | 6x+15=3+8x-8 | | 2+6xt=-9 | | 3x^2-5x+2=4x+2 | | b=a^3-(a-3) | | 4(x+1)/8=3x-2 | | p=2x^2+18x+332 | | 2A+4=16 | | 7x+25x^2+4=5+7x | | 2x+7(3x-13)=47 | | 9(X-1)+X=8(3-X)-6 | | 0.04+X=74.52 | | y+2=-6/5+6/5 | | 13+2r=3r+7 | | 3(5-x)=9(15x-5) | | x/8=54 | | 3.75+3y=6 | | f(x)=8-7(4x+2) |

Equations solver categories